PENGARUH SELF EFFICACY TERHADAP AUDIT JUDGEMENT DENGAN SENIORITAS AUDITOR SEBAGAI PEMODERASI ( Studi Kasus pada Inspektorat Kota Bogor dan Depok ) - Yunita Kurnia Shanti (JURNAL AKUNTANSI BARELANG, 2019)
This research aimed was to examine the impact of self efficacy on audit judgement with auditor senior as moderate variable at inspectorat of bogor city and depok city. This research is done to prove the influence of these variable on audit judgement. This population is goverment internal auditor at inspectorat of bogor city and depok cityS in west java. Samples were taken by convenience sampling pursuant to amenity acces and availability of respondent. Amount of sample is 41 respondent can be to test. Statistical data analysis method used is simple linear regression and multiple regression analysis. The hypotesis of this research is divided into two, self efficacy of audit judgement, and self efficacy on audit judgement with auditor senios as moderate variable. The result of this research shows that self efficacy have significant influenced on audit judgement. It means more auditors is confident in capability they have, will be better the audit judgement. Self efficacy have no significant influenced on audit judgement with senior auditor as moderate variable. Its show that audit judgement must be supported by self confident but not only carried out by the senior auditor but all auditors in the audit assignment.